2020
DOI: 10.1136/bmjmilitary-2020-001571
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness and anthropometrics in Finnish soldiers during their early career: prospective changes during a 3-year follow-up

Abstract: IntroductionPhysical fitness is a fundamental capability required of military personnel, but studies focusing on longitudinal changes in physical fitness and anthropometrics in soldiers are lacking. The aim was to evaluate physical fitness and anthropometrics in soldiers during their early career.MethodsA 3-year prospective study included 180 male soldiers (baseline age 26±2 years) with measures of a 12 min running test, standing long jump, sit-up and push-up tests, and body mass, height and waist circumferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Despite approximately 63% of the sample having been classified as "good" and "excellent" cardiorespiratory fitness, the average presented in the 12-minute test (2765 ± 231.8 m) shows acceptable indexes for cardiorespiratory fitness, constituting a superior result to others found in the literature. As an example, higher values were observed in the 12-minute test in this study when compared to FAB military personnel from a Military Organization located in southern Brazil (2485.3 ± 322.4m) (Pereira & Teixeira, 2006), as well as being superior to those presented by Finnish military personnel (also recruits), who presented an average of 2661 ± 191m (Vaara et al, 2020). When compared with subjects with similar ages to those in the present study, similar values to those of FAB recruits in the final training period were identified (2752 ± 217m) (Campos et al, 2017).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Despite approximately 63% of the sample having been classified as "good" and "excellent" cardiorespiratory fitness, the average presented in the 12-minute test (2765 ± 231.8 m) shows acceptable indexes for cardiorespiratory fitness, constituting a superior result to others found in the literature. As an example, higher values were observed in the 12-minute test in this study when compared to FAB military personnel from a Military Organization located in southern Brazil (2485.3 ± 322.4m) (Pereira & Teixeira, 2006), as well as being superior to those presented by Finnish military personnel (also recruits), who presented an average of 2661 ± 191m (Vaara et al, 2020). When compared with subjects with similar ages to those in the present study, similar values to those of FAB recruits in the final training period were identified (2752 ± 217m) (Campos et al, 2017).…”
Section: Discussionmentioning
confidence: 42%
“…Likewise, higher cardiorespiratory fitness levels need to be maintained during their careers, which demands that military personnel are periodically submitted to physical tests and body analyses, regardless of the nature of the assignments performed (operational or support), rank/graduation, or gender (Knapik, 1989;Avila et al, 2013;Vaara et al, 2020). Regular physical tests have the function of verifying the physical conditions of the military in relation to the minimum standards required for the proper exercise of their operational demands.…”
Section: Introductionmentioning
confidence: 99%